2010
DOI: 10.1097/psy.0b013e3181ecd08a
|View full text |Cite
|
Sign up to set email alerts
|

Couples' Nighttime Sleep Efficiency and Concordance: Evidence for Bidirectional Associations With Daytime Relationship Functioning

Abstract: Objective Emerging evidence suggests the existence of bidirectional links between sleep and relational processes in dyads, but to date, this research has been primarily cross-sectional. The present analyses were undertaken to prospectively examine the directionality of the association between daily relationship functioning and nightly sleep quality and the association between couples’ relationship functioning and concordance in sleep-wake rhythms. Methods Sleep was measured via both diaries and wrist actigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 29 publications
14
141
2
Order By: Relevance
“…This may be the reason of disagreement between the questionnaire and actigraphic measure of sleep latency among wives. On the other hand, this finding may reveal the presence of the same, but weaker, paradoxical situation for spouses, and most probably demonstrates the effects of the veterans' sleep situations on the sleep quality of their wives, which was hypothesized, however, not directly studied by previous investigators (7,26,27). Therefore, we could propose that the wives' shared paradoxical insomnia is induced by their husbands' sleep problems.…”
Section: Discussioncontrasting
confidence: 37%
“…This may be the reason of disagreement between the questionnaire and actigraphic measure of sleep latency among wives. On the other hand, this finding may reveal the presence of the same, but weaker, paradoxical situation for spouses, and most probably demonstrates the effects of the veterans' sleep situations on the sleep quality of their wives, which was hypothesized, however, not directly studied by previous investigators (7,26,27). Therefore, we could propose that the wives' shared paradoxical insomnia is induced by their husbands' sleep problems.…”
Section: Discussioncontrasting
confidence: 37%
“…Insomnia is associated with mood disturbances (e.g., irritability), heightened emotional reactiveness [60][61], negative interactions with children [62] and partners [63], reduced optimism and self-esteem [64], and overall poor quality of life (e.g., vitality) [61].…”
Section: Short-term Consequences Of Insomniamentioning
confidence: 99%
“…We also aimed to explore gender differences in preferred time of day for sexual activity, as no such direct comparison has been reported so far -previous studies have considered mostly pairs with no distinction on gender. Previous studies have shown that sleep patterns may both influence and be influenced by interpersonal interactions in couples (Hasler & Troxel, 2010;Troxel et al, 2007), thus the stated questions seem important when considering sexual and relationship satisfaction for partners with different chronotypes.…”
Section: Introductionmentioning
confidence: 99%